The perception of chromatic stimuli in the peripheral human retina - McKeefry, Declan J.; A. Parry, Neil R.; Murray, Ian J.; Panorgias, Athanasios (Psichologija, 2008)
We have studied the changes that occur in human colour perception in the peripheral retina. By modelling the magnitude of activation produced in the L-M and S-(L+M) cone-opponent systems for matched para-foveal and peripheral chromatic stimuli, we have found that variations in perceived appearance are mirrored by a reduction in function of the L-M opponent system. The operation of the S-cone opponent system is affected to a much lesser degree, implying that there is a changing pattern of predominance between the two cone-opponent mechanisms in the peripheral retina. We will explore possible retinal and cortical bases for these changes.